RELIGIOUS TRANSFORMATION OF SENI DODOD TAKING PLACE AT MEKAR WANGI VILLAGE SOUTH BANTEN - Kasmahidayat, Yuliawan; Dibia, I Wayan; Alwasilah, A. Chaedar; Suastika, I Made (E-Journal of Cultural Studies, 2012)
Religious transformation of Seni Dodod taking place at Mekar Wangi Village, SaketiDistrict, Pandeglang Regency, South Banten, Banten Province enriches the analysis of thecommunity cultural pattern based on the art characteristics born and developing in thecommunity. In relation to that, this study describes the cultural phenomenon of religioustransformation as the ideological basis of the pre-modern, modern and postmodern communities.Multidisciplinary qualitative method was employed in this study and the data needed werecollected by in-depth interview, participatory observation and documentation techniques. Thefindings show that the Seni Dodod has the belief or the religion adhered to by the people living atMekar Wangi Village as its religious background. Such a belief affects the relation patternbetween the individuals and their community, nature and God. This is used as the reference inwhat is done in the agricultural process, making Seni Dodod a cult and realizatrion. When thecultural transformation process was taking place, it was found that there was a point of contactbetween traditional arts and modern arts outside the domain of Seni Dodod . Nowadays newcompositions of Seni Dodod have been created functioning as instruments of wedding andkhitanan rituals (khitanan = a feast celebrating a circumcision). The process of acculturation wasformally performed at school by using its compositions as the learning material of art andculture. Its application in its original form and composition was informally inherited throughSeni Dodod studios, the youth and villagers. Its religious meaningfulness was reflected from thecountry life performed by the people living at Mekar Wangi village. Such meaningfulness wasbased on that given by the leaders of pondok pesantren (Muslem boarding school) and on theexplanation clarifying, showing, separating and elaborating seven clauses of Al-Qur’an. Themeaningfulness provided resulted in intactness of movements, the costumes worn, the poem oflutung kasarung , the magic formula or the prayers used. In addition, it was also referred to asMuslim art and culture. It seems that nowadays a shift has taken place as far as its function isconcerned. It used to be employed as a means of agricultural ritual but now it has been animportant part of wedding and khitanan rituals; however, it has not been employed as a secularart
Keywords: Transformation, religious, Seni Dodod